Analysis of Constraints faced by State Agricultural Management and Extension Training Institutes (SAMETIs) : An Empirical Study - G. Jaya; G. Dileep Kumar (Journal of Agricultural Extension Management, 2021)
State Agricultural Management and Extension Training Institutes (SAMETIs) are the autonomous institutes to look after the extension and training related aspects of middle, grassroot level extension functionaries and also farmers. The present paper discusses the constraints faced by various SAMETIs in terms of Infrastructure, Human Resources, Financial Matters, Administrative aspects, and constraints in operating the Central Sector Plan Schemes like Diploma in Agricultural Extension Services for Input Dealers (DAESI), Skill Training of Rural Youth (STRY), further also in the conduct of the Post Graduate Diploma in Agricultural Extension Management (PGDAEM). A structured questionnaire was administered and data collected through a mailed survey from about 31 SAMETI Directors across the country. Weighted averages were calculated to know where a particular constraint falls on a continuum of 1 to 5 (Strongly Disagree to Strongly Agree). The results of the study implied that there are significant measures which may be taken to improve the condition of SAMETIs to make them more vibrant and serve the farmers with vigour and passion